PEMBUATAN APLIKASI ALAT MUSIK TRADISIONAL GAMBANG - Florencia Gleda; Fitri Dwi Kartikasari; Andre Andre (CALYPTRA, 2018)
Indonesia is a country with a rich culture, one of them is the traditional musical instrument gambang. Gambang is a traditional musical instrument from Central Java. From the results of questionnaire, there are many respondents who didn’t know the shape, how to play and where gambang came from. Respondents also said that they rather play modern musical instruments than the traditional one. Those are the backgrounds which are made for the making of traditional musical instrument gambang application. The name of this application is Dolanan Gambang, where this application is intended for Indonesian citizens to understand about gambang and play it virtually with leap motion as an input. Users can play gambang with traditional/modern songs. This application are made with Adobe Flash Professional CS 6, Adobe Photoshop CS 6, Adobe audition CS 6, Autodesk 3DS Max 2015, C# dan Unity 5.5. Results of verification and validation shows that this application is working well. From questionnaire results, many respondents said they agree that this application can increase their knowledge about gambang. This application can also provide an experience of playing gambang virtually. Respondents also said that this application have an easy to understand interface and it is visually appealing. Although at first respondents seems to have a hard time playing because they are not used to using leap motion. Furthermore, respondent tells that this application made them interested on playing gambang.